The working characteristics of electric field measurement based on the Pockels effect for AC–DC hybrid fields. (30th October 2018) - He, Bo; Liu, Shuming; Zhu, Pengfei; Li, Yifei; Cui, Donggang
Abstract: Though electrical field measurement based on the Pockels effect has shown good prospects for application, the accuracy and stability of the measurements have not been studied in depth. Especially with AC–DC hybrid fields, there are few reports on the performance of measurements. In this paper, a special optical path was set up in the laboratory, and the major working characteristics of hybrid electric field measurement, such as accuracy, long-term stability, linearity, and so on, were examined through experiments using the polarization characteristics of a crystal. The results show that the DC component of the hybrid field causes a smaller measurement result of the AC component, and the greater the DC component, the greater the deviation. In addition, there is good linearity between the measurement output and AC component when the DC component is fixed. The results are promising for future use in sensor design, precision compensation, and calibration in hybrid electric field measurement.